Epidural Fat and Perineural Adipose Tissue Septic Emboli Mimicking Peripheral Nerve Sheath Tumor in a Dog - Yael Merbl; Kelly M. Ramsay; Ashley Hanna; Annie V. Chen; Laura Anne White; Claire R. Burbick (Case Reports in Veterinary Medicine, 2022)
Summary. A 9-year-old 35.6 kg (90 lb) female neutered German Shepherd dog was admitted due to progression of tetraparesis. The dog presented pyrexia, mild leukocytosis, and nonambulatory tetraparesis with decreased general proprioception and withdrawal in all the limbs, with the front limbs more severely affected. Magnetic resonance imaging revealed T2-weighted image (WI) hyperintense, contrast-enhancing lesion at the level of the C6-C8 spinal nerves, and epidural fat, suspected to be an infiltrative neoplasm. Medical treatments during hospitalization included glucocorticoids, antibiotics, and supportive care. Euthanasia was elected 4 days later due to financial constraints, despite clinical improvement. Postmortem findings revealed septic emboli (SE) in the epidural fat exiting the canal and following the tract of the spinal nerve roots and nerves. Staphylococcus pseudintermedius was identified as the causative agent. Although the incidence of SE without severe systemic disease is considered low in dogs, it should be considered in the differential diagnosis of focal intraspinal disease.